RESEARCH ON THE TECHNIQUES FOR CUTTING OF CINNAMOMUM BALANSAE - Ngoc Hai, Tran; Huu Nghi, Dang; Dinh Phuong, Le; Van Hoang, Tong (Journal of Forestry Science and Technology, 2017)
Cinnamomum balansae is an endemic, rare species of tree in Vietnam, was rated level EN by IUCN, VU by the Vietnam Red Book – 2007 and classified as group IIA by Decree 32/2006/NĐ-CP. Besides its natural regeneration capacity is very limited so conservation and development for this species are facing a big challenge of seedling shortages. Therefore, study of breeding Cinnamomum balansae is extremely necessary. The vegetable breeding technology for Cinnamomum balansae by branch cutting in Ben En National Park gave good results. Using AIA and ABT1 chemicals in different concentrations showed that: The highest rate of rooting of the cuttings after 60 days belongs AIA 1.5%, reaching 65%, followed by ABT1 1.5% and AIA1.0% with 60% for both. Growth stimulants are also a positive effect on the quality of the roots. In which AIA at concentrations of 1.0%, 1.5% and ABT1 1.5% always give the roots the best quality. The study results also confirm that the growth rate in the nursery stage is relatively slow, after 6th months of taking care, Cinnamomum balansae can meet the standards of being exported from the nursery, however it is recommended to lengthen the time in the nursery until the 10th month to train the trees to ensure the quality and survival rate for afforestation.